Technology-integration strategies for accommodating learning style differences in young learners’ English-speaking class - Ardiana, Kadek Fery; Arum Sari, Valentina Dyah (Politeknik Negeri Jember, 2025)
Technology in education has become an essential component in enhancing the learning experience, particularly for young learners in this digital era. By leveraging digital tools, educators can create dynamic and engaging environments that cater to diverse learning needs. This study aimed to reveal the implementation and find out the benefits of technology applications (Puzzlemaker, Wordwall, Bamboozle, and YouTube) for the fifth graders in learning English-speaking skills; within the Merdeka curriculum framework. Using a mixed-methods approach, the data were collected through interviews and questionnaires. The qualification of implementation and the benefits of the technology integration in speaking skills were analyzed by using Sugiyono's (2009) percentage formula. The result showed that technology applications achieved 63.8% for the implementation and 65.2% for the benefits; respectively categorized as moderate. Furthermore, technology integration is an innovative technique to helping young learners to learn English-speaking skills by combining game-based applications. Students may interact more actively with the topic while also encouraging cooperation and critical thinking, making learning more dynamic and engaging.